"Helping someone with a skill sharpens it in your own mind": a mixed method study exploring health professions students experiences of Peer Assisted Learning (PAL). Issue 1 (December 2016) - Carr, Sandra; Brand, Gabrielle; Wei, Li; Wright, Helen; Nicol, Pam; Metcalfe, Helene; Saunders, Julie; Payne, John; Seubert, Liza; Foley, Laurie
Abstract Background Peer assisted learning (PAL) has been described as "the development of knowledge and skill through active help and support among status equals or matched companions". To enhance the learning experience of health professions students and improve collaborative and collegial learning, six pilot Peer Assisted Learning (PAL) projects were conducted across a health science faculty. Methods A responsive mixed method evaluation design was applied to explore the adequacy of the preparation for PAL, the impact PAL had on student attainment of examination, consultation, communication and feedback skills and to explore students' learning experiences through PAL. Results The 149 participants agreed the training programme was well organised, offered a safe learning environment and prepared the participant for the PAL activity. The impact of PAL included improvements in students' confidence and ability to give feedback and developed students' teaching, clinical and communication skills. Qualitative analysis revealed participants experienced deeper learning through teaching and learning from their peers, became more open to giving and receiving feedback and valued the comfortable/safe learning environment offered through PAL. Conclusion Providing appropriate training in peer teaching and feedback and the schools engagement and openness to peer learning in the classroom and clinical setting enhances students' peer assisted learning experience.